Excretion of myoglobin in urine after cardiac catheterisation. - Donald, T G (Br Heart J, 1978)
Myoglobin levels were assayed in each urine specimen voided during 12 hours before and 48 hours after routine cardiac catheterisation in 146 patients using an indirect haemagglutination method detecting concentrations in excess of 0.015 mg/ml. Myoglobinuria was found in only one patient before but in 39 patients after cardiac catheterisation (27%), either in the first (34 patients) or the second (5 patients) post-catheterisation urine sample. Once detected, myoglobin was present in all subsequent urine specimens for the next 3 to 22 hours (mean 11.8 hours). The mean amount excreted +/- SE was 14.0 +/- 1.6 mg (range 2.6 to 30 mg) excluding the one patient with myoglobinuria before catheterisation. This patient, who had severe aortic stenosis and atherosclerotic heart disease, excreted 130 mg myoglobin. Patients with myoglobinuria required longer screening time to complete the procedures undertaken than those in whom myoglobin was not detected--15.6 +/- 1.4 and 11.1 +/- 0.6 minutes, respectively (mean +/- SE:P less than 0.01). We conclude that myoglobinuria is not uncommon after cardiac catheterisation, and that though the myoglobin detected may be released from skeletal muscle, it could be partly or wholly of cardiac origin and indicate transient, and presumably reversible, myocardial injury.